Proper and incorrect body posture in students from music schools - Roland Hadlich (Kazimierz Wielki University, 2017)
Introduction. The basic activity of a musician playing an instrument is movement and the related physical work of specific muscle slings. With contemporary curricula to teach playing instruments and the related load to the bone, muscular, cardiovascular and nervous systems, several properties of the specific physical activity should be taken into account. Material and Method. The statistical analysis concerned 190 girls and 203 boys. Mean age of the girls was 14.25 years, with mean playing experience of 7.25 years. The test stand for evaluation of body posture and feet using the photogrammetric method is composed of a personal computer, software, screen and printer, projection-reception device with a camera for measurement of selected characteristics. Conclusion 1. Long-term regular playing an instrument has a major effect on the angle of body bent in the sagittal plane. 2. Playing six of the analysed instruments leads to deepening of physiological spinal curvature: 3. The magnitude of selected sagittal spinal characteristics in students from music schools found in the study suggests implementation of prevention and correction programs. Wstęp. Podstawową aktywnością muzyka w czasie gry na instrumencie jest ruch i związana z tym praca fizyczna wybranych taśm mięśniowych.. Współczesny proces nauczania gry na instrumencie i związane z nim obciążenia układu kostnego, mięśniowego, krwionośnego i nerwowego wymagają uwzględnienia szeregu właściwości realizowanej aktywności fizycznej Materiał i metoda. Do analizy statystycznej zakwalifikowano 190 dziewcząt i 203 chłopców. Średnia wieku wśród dziewcząt wynosiła 14,25 roku, a staż gry 7,25 roku. Stanowisko do pomiaru wielkości cech postawy ciała i stóp metodą fotogrametryczną składa się z komputera i karty, programu, monitora i drukarki, urządzenia projekcyjno - odbiorczego z kamerą do pomiaru wybranych cech. Wnioski 1. Wymuszona i długotrwała gra na wybranym instrumencie wpływa głownie na kąt zgięcia i wyprostu tułowia w płaszczyźnie strzałkowej. 2. Wykonawstwo na sześciu analizowanych instrumentach powoduje pogłębienie krzywizn fizjologicznych kręgosłupa: 3. Stwierdzone wielkości wybranych cech strzałkowych kręgosłupa u uczniów szkół muzycznych wymaga wprowadzenia postępowania profilaktyczno-korekcyjne.